Assessing mRNA Integrity using Capillary Electrophoresis: Insights into Scientific Parameters - Souza, Raysa Silva de (2024)
Fundação Oswaldo Cruz. Instituto de Tecnologia em Imunobiológicos (Bio-Manguinhos). Rio de Janeiro, RJ, Brasil.